Preparation and characterization of cisplatin-incorporated chitosan hydrogels, microparticles, and nanoparticles - Cha, Jueun; Lee, Won Bum; Park, Chong Rae; Cho, Yong Woo; Ahn, Cheol-Hee; Kwon, Ick Chan (POLYMER SOC KOREA, 2006)
Three different, polymer-platinum conjugates (hydrogels, microparticles, and nanoparticles) were synthesized by complexation of cis-dichlorodiammineplatinum(II) (cisplatin) with partially succinylated glycol chitosan (PSGC). Succinic anhydride was used as a linker to introduce cisplatin to glycol chitosan (GC). Succinylation of GC was investigated systematically as a function of the molar ratio of succinic anhydride to glucosamine, the methanol content in the reaction media, and the reaction temperature. By controlling the reaction conditions, water-soluble, partially water-soluble, and hydrogel-forming PSGCs were synthesized, and then conjugated with cisplatin. The complexation of cisplatin with water-soluble PSGC via a ligand exchange reaction of platinum from chloride to the carboxylates induced the formation of nano-sized aggregates in aqueous media. The hydrodynamic diameters of PSGC/cisplatin complex nano-aggregates, as determined by light scattering, were 180-300 run and the critical aggregation concentrations (CACs), as determined by a fluorescence technique using pyrene as a probe, were 20-30 mu g/mL. The conjugation of cisplatin with partially water-soluble PSGC, i.e., borderline between water-soluble and water-insoluble PSGC, produced micro-sized particles < 500 mu m. Cisplatin-complexed PSGC hydrogels were prepared from water-insoluble PSGCs. All of the cisplatin-incorporated, polymer matrices released platinum in a sustained manner without any significant initial burst, suggesting that they may all be useful as slow release systems for cisplatin. The release rate of platinum increased with the morphology changes from hydrogel through microparticle to nanoparticle systems.
Keywords: N-SUCCINYL-CHITOSAN; MACROMOLECULAR THERAPEUTICS; POLYMERIC MICELLE; HPMA COPOLYMER; DRUG CARRIER; MICROSPHERES; RELEASE; CIS-DICHLORODIAMMINEPLATINUM(II); DOXORUBICIN; DELIVERY